Principle of Proportionality and Classification of Measures Implementing the Principle of Proportionality in the Context of Interim Measures - Doržinkevič, Artur (Teisė, 2022)
This article analyzes the application of the principle of proportionality in the context of interim measures. The study reveals how and to what extent is the principle of proportionality regulated by law in the application of interim measures. The author distinguishes measures implementing the principle of proportionality in the context of interim measures according to different criteria: (a) the nature of the issue; (b) the subject carrying out the proportionality assessment; (c) the time (stage) at which the proportionality assessment is carried out. For this study, the author analyzed the case law of both the Lithuanian Court of Appeal and the European Court of Human Rights regarding the proportionality of the restriction of property rights in the context of interim measures.
Keywords: interim measures; provisional measures; civil procedure; principle of proportionality